2010
DOI: 10.1016/j.fsi.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of laccase activity in the Pacific oyster Crassostrea gigas

Abstract: Phenoloxidases (POs) are a family of enzymes including tyrosinases, catecholases and laccases, which play an important role in immune defence mechanisms in various invertebrates. The aim of this study was to thoroughly identify the PO-like activity present in the hemolymph of the Pacific oyster Crassostrea gigas, by using different substrates (i.e. dopamine and p-phenylenediamine, PPD) and different PO inhibitors. In order to go deeper in this analysis, we considered separately plasma and hemocyte lysate super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 50 publications
2
50
1
Order By: Relevance
“…In a previous study, catecholase-type PO activity was detected in the haemolymph of C. gigas with L-DOPA and dopamine as substrates [13]. However, in the present study, dopamine displayed a toxic effect, while L-DOPA displayed no toxic effect on LGP32, when used alone at 1.25 mM concentration (data not shown).…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…In a previous study, catecholase-type PO activity was detected in the haemolymph of C. gigas with L-DOPA and dopamine as substrates [13]. However, in the present study, dopamine displayed a toxic effect, while L-DOPA displayed no toxic effect on LGP32, when used alone at 1.25 mM concentration (data not shown).…”
Section: Resultscontrasting
confidence: 65%
“…In a previous study, laccase-type PO activity was detected in the haemolymph of C. gigas in the presence of the non phenolic substrate, PPD, but neither in the presence of the methoxy phenolic substrate, 4-hydroxy-3,5-dimethoxybenzaldehyde azine (syringaldazine), nor in the presence of the non phenolic substrate, 2,2 0 -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) [13]. However, since PPD exerted an effect on bacterial growth in the absence of HLS in the present study (data not shown), results were expressed as the percentage of inhibition due to HLS (Table 1).…”
Section: Effect Of Po-generated Reactive Intermediates On the Growth mentioning
confidence: 96%
See 1 more Smart Citation
“…However, the presence of ultraviolet (UV) and visible-lightabsorbing melanin may be advantageous during times of temperature stress [8]. Laccase activity within anthozoans is therefore likely to be involved in clot stabilization [19] or another aspect of immunity, as hypothesized for the Pacific oyster, which also lacks an integument [22].…”
Section: Discussionmentioning
confidence: 99%
“…While the tyrosinase-type melanin synthesis pathway has been the most intensively investigated with regard to invertebrate immunity [48,49], an invertebrate laccase-type pathway has also been documented [50]. However, aside from a likely role in cuticle formation, roles of the laccase-type pathway remain to be elucidated [46,50].…”
Section: (Iii) Integrinsmentioning
confidence: 99%